PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN PICTURE AND PICTURE PADA SISWA KELAS 2 - Mega Wahyuningsih (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2021)
Abstract Picture and picture learning model is a learning model which can help learning Social Studies. Where the teacher uses media such as images to explain a material or facilitate students to learn actively and aims to improve the activities and learning outcomes of 2nd graders at SD Negeri Medani 02, Cluwak, Pati. The benefits that can be obtained are increasing knowledge and broadening horizons for researchers in particular and for educators in general regarding interesting learning models and learning media so as to further increase students' interest in learning. Subjects in this study are teachers and 2nd graders of Medani 02 Cluwak, Pati. 1 teacher and 12 students consisting of 6 male students and 6 female students. Sources of data from this study came from teachers, students, document data and field notes. The results of the implementation of the first cycle of research showed an increase. The average student learning outcomes became 71.42 with the lowest score is 50 and the highest score is 90. 4 students had not reach the KKM yet and 10 students had reached the KKM. The percentage of student completeness is 71.42% and 28.58% of students who have not. In the second cycle of research showed an increase in the average student learning outcomes to 88.57 with the lowest score is 70 and the highest score is 100. All students had reached the KKM. The percentage of student completeness is 100%. From these results it can be concluded that the predetermined success indicators have been achieved. Keywords: Picture and picture learning model, Social studies, learning outcomes.